Unmet needs in the management of abnormal uterine bleeding: insights from social media listening - Marcelo Graziano Custodio; Hisham Arab; Andressa da Silva van der Laan; Natalia Pedachenko; Qinjie Tian; Maria Celeste Osorio Wender; Tony Piha; Rubina Sohail; Fernando Pineda; Jobert Neves; Rishma Dhillon Pai; Tommaso Simoncini (Gynecological Endocrinology)
Background Abnormal uterine bleeding (AUB) impacts the quality of life of women globally. While international classifications and frameworks exist, there are still critical unmet needs in awareness, diagnosis, treatment, and patient support. To better understand these, the lived experiences of patients with AUB shared on social media can offer valuable insights.Objective To identify and analyze unmet needs in the management of AUB as expressed during social media discussions.Methods Using the social media listening tool Sprinklr Social (Sprinklr Inc.), public posts from X (X Corp.) related to AUB from seven countries (Brazil, China, India, Mexico, Pakistan, Saudi Arabia, Ukraine) over a 10-year period (2014–2024) were analyzed. Posts were categorized by topic, sentiment, and emotion; further analyses assessed patients’ unmet needs and feelings.Results A total of 926 posts were included. Analysis revealed five critical unmet needs: lack of awareness and understanding (41.8%), impact on wellbeing (27.6%), diagnosis issues (10.9%), dissatisfaction with treatment options (9.7%), and undervalued impact and advocacy (8.6%). Posts about diagnosis and symptoms carried the most negative sentiments; many patients expressed frustration over delayed diagnoses and dissatisfaction with treatment options. Additionally, the emotional and psychological burden of AUB was a recurring theme, suggesting the need for more holistic care approaches.Conclusions Gaps in AUB management were identified, with strong emphasis on the need for better patient education, more effective diagnostic processes, and personalized treatment strategies. Incorporating patient voices during the development of treatment guidelines and healthcare policies is crucial for addressing these unmet needs and improving patient outcomes.